Quality improvement of mango ketchup (Mangifera indica L.) using jackfruit seed (Artocarpus heterophyllus Lam.) flour. - Bation, Angeli Aala
The study was focused on quality improvement of mango ketchup using jackfruit seed flour (JSF). JSF with water activity of 0.52 and a moisture content of 7.79 was utilized to prepare three formulations of mango ketchup with different concentrations of JSF. F1 with 5% JSF with respect to mango puree, F2 with 10% and F3 with 15% were subjected to rank test for preference. F1 was significantly preferred (Kramer?s Rank Test at α=0.05) compared to F2 and F3. The mango ketchup prepared from the formulation F1 also designated as F1 was characterized together with the control. Properties analyzed include physico-chemical (pH, water activity (aw), total soluble solids (TSS), titratable acidity (TA), proximate composition (moisture content, crude protein, crude fiber, crude fat, ash and carbohydrates), consistency test, and stability test. Data were analyzed using t-test at 5% level of significance. JSF significantly reduced the aw of mango ketchup from 0.962 (control) to 0.958 (F1), and the pH from 3.52 (F1) to 3.49 (control). JSF significantly increased the TSS from 25.17 °Bx (control) to 27.05 °Bxx (F1), however JSF did not significantly alter the TA of the mango ketchup. Incorporation of jackfruit seed flour significantly improved the nutritional value of mango ketchup. Ash content significantly increased from 5.40% (control) (F1). There was also a significant increase in protein content and crude fiber from 0.53% (control) to 0.94% (F1), however JSF did not significantly alter the TA of the mango ketchup. Incorporation of jackfruit seed flour significantly improved the nutritional value of mango ketchup. Ash content significantly increased from 5.40% (control) to 5.95% (F1). There was also a significant increase in protein content and crude fiber from 0.53% (control) to 0.94% (F1) and from 8.22% (control) to 8.48% (F1), respectively. JSF significantly reduced the carbohydrate content from 10.37% (control) to 9.47% (F1), however JSF did not significantly reduced the carbohydrate content from 10.37% (control) to 9.47% (F1), however JSF did not significantly affect the moisture content and crude fat content of mango ketchup. F1 had a significantly thicker consistency (10.42 cm/30s) than the control sample (13.05 cm/30s). F1 obtained a rating of like very much and was significantly preferred over the control sample. Among the 100 consumers, only 20% of the total respondents rated the product like extremely, 36% liked the product very much, 32% rated F1 like moderately, 10% liked it slightly and 2% rated F1 neither like nor dislike. Based on these ratings, mango ketchup with 5% JFS.